CIPP-Based Evaluation of Occupational Health Services in Wijirejo Batik Industry, Pandak, Bantul, Indonesia - Haqifa Rosyida Putri; Heru Subaris Kasjono; Ibnu Rois; Sugianto Sugianto (Poltekkes Kemenkes Tanjung Karang, 2026)
Batik workers are vulnerable to occupational health problems caused by chemical exposure, non-ergonomic working postures, and inadequate use of Personal Protective Equipment (PPE). At the Giriloyo Batik Center in Bantul, 57.9% of workers reported skin disorders, particularly dermatitis, associated with repetitive work activities. Occupational Health Services Posts (OHS Posts) have been introduced to improve the health status of informal-sector workers; however, comprehensive evaluations of their implementation in the batik industry remain scarce. This study evaluated the implementation of the OHS Post in Wijirejo, Pandak, Bantul, using the Context, Input, Process, and Product (CIPP) evaluation model. A mixed-methods evaluative study was conducted in two batik industries in Wijirejo Village, Bantul. Data were collected through observations, questionnaires, in-depth interviews, and documentation. Program performance was assessed using the CIPP framework. Quantitative data were analyzed descriptively, while qualitative data were processed through data reduction, data display, and conclusion drawing. The findings indicated that the work environment generally complied with occupational safety standards, although risks related to musculoskeletal disorders and chemical exposure persisted. Human resources met the requirements of Permenkes No. 100 of 2015; however, cadre training had not been implemented, and funding relied solely on the state budget. Program activities were conducted regularly, but administrative functions remained dependent on the OHS Post supervisor. Overall, the OHS Post was classified as Intermediate (Madya), with improvements in workers’ behavior (43.8%) and occupational health knowledge (37.5%), while the reduction in occupational disease cases remained limited (18.8%). The OHS Post contributed positively to improving occupational health awareness and behavior among batik workers. Strengthening cadre competencies, administrative systems, promotive-preventive activities, and sustainable funding is essential to enhance long-term program effectiveness.